2012
DOI: 10.1111/j.1365-2362.2012.02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury results from failure of neutrophil de‐priming: a new hypothesis

Abstract: Neutrophils are the most abundant circulating white cell in humans and play a crucial role in the innate immune response. Accumulation and activation of neutrophils, together with delayed clearance, have been shown to be a key event in the pathogenesis of acute lung injury. Previously, it has been proposed that there is substantial pooling of neutrophils within the pulmonary vasculature, even under physiological conditions, making the lung especially vulnerable to neutrophil-mediated tissue injury. However, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 69 publications
(96 reference statements)
3
36
0
1
Order By: Relevance
“…The pulmonary endothelium plays an active role in regulating the priming of PMNs during their transit through the systemic circulation (Aoyama-Ishikawa, et al 2014, Singh, et al 2012). In the mouse model of sepsis, the pro-inflammatory milieu caused by endotoxin challenge impairs lung-mediated PMN de-priming, resulting in their accumulation, priming, release to the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary endothelium plays an active role in regulating the priming of PMNs during their transit through the systemic circulation (Aoyama-Ishikawa, et al 2014, Singh, et al 2012). In the mouse model of sepsis, the pro-inflammatory milieu caused by endotoxin challenge impairs lung-mediated PMN de-priming, resulting in their accumulation, priming, release to the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy pulmonary endothelium instructs the primed cells to ‘de-prime’ and return back to a quiescent state within the vasculature [25]. It is only when neutrophils confront activated markers on the pulmonary endothelium such as P-selectin, ICAM-1, etc., will they adhere to the endothelium and become activated [26].…”
Section: Discussionmentioning
confidence: 99%
“…Reversible priming was also shown by priming neutrophils by TNFα and PAF . Summers and colleagues showed that unprimed neutrophils are not or weakly retained in human pulmonary vessels, but primed neutrophils are markedly retained, then deprimed and released into the circulation . Thus, in healthy individuals, neutrophils can be physiologically primed, activated, deactivated, and finally can die by apoptosis ( Fig.…”
Section: Reversible Priming or ‘Depriming’mentioning
confidence: 99%